BIOINFORMATION TECHNOLOGIES IN PLANT BREEDING - Urazaliev , K.R. (Eurasian Journal of Applied Biotechnology, 2018)
Plants are comprised of a complex network of interrelated characteristics, where a change in one characteristic may cause a change in another, or in a combination of characteristics. Crop breeding techniques for selection of specific characteristics is largely constrained by insufficient theoretical levels in many branches of modern genetics, the basis of which should be corresponding mathematical models. Development of mathematical models for quantitative characteristics in "genotype-environment" systems, using molecular- and bio-technology in plant breeding can help to significantly reduce the time and cost required to create new varieties of agricultural plants, and can significantly improve breeding efficiency by constructing reliable predictive estimates and identifying selected genotypes.